Factors affecting attitude and intention to use islamic banking in Indonesia - Widuri Tyas Utami; Ferryal Abadi (LPMP Imperium, 2022)
This research aimed to examine factors affecting attitude and intention to use IB and to confirm customer decision-making. With the purposive sampling method, 165 valid responses from Muslim customers were analyzed using PLS-SEM. The data were collected in Jabodetabek cities and around using an online questionnaire during the pandemic covid in December 2021. The study revealed that sharia compliance, uncertainty avoidance, corporate image, customer attitude, and intention to use IB significantly and positively influenced, but customer awareness and the moderation role of religiosity did not influence.